2003
DOI: 10.1046/j.1474-9728.2003.00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic regions responsible for manganese superoxide dismutase regulation in Drosophila melanogaster

Abstract: SummaryThe transcription of manganese superoxide dismutase ( MnSOD ), expression of which is essential for detoxification of superoxide radicals from mitochondria, has been shown to be regulated in vitro by many factors and conditions including oxidative stress, cytokines, lipopolysac-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…KG06854R shares the same genetic background as Sod2 n283 . 47 Chi-square independence test was performed at 95% confidence interval by feeding the data into the University of Kansas web site http:// www.people.ku.edu/~preacher/chisq/chisq.html.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…KG06854R shares the same genetic background as Sod2 n283 . 47 Chi-square independence test was performed at 95% confidence interval by feeding the data into the University of Kansas web site http:// www.people.ku.edu/~preacher/chisq/chisq.html.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Shen, Li, et al ( 2013 ) and Shen, Xiao, et al ( 2013 ) reported that D. melanogaster has a region that encodes enhancement of SOD activity and four regions that encode suppression of SOD activity. Disruption of gene encoding SOD in D. melanogaster has been shown to reduce SOD activity (Paul & Duttaroy, 2003 ; Woodruff‐Pak et al, 2001 ). Overexpression of this gene, however, resulted in increased SOD activity in D. melanogaster (Aigaki et al, 2002 ; Sun et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%